(untitled) (Psychology Travelogs, 2024)
The article presents a theoretical study of the causes of conflicts between marital partners during pregnancy planning, emphasizing the importance of comprehensive preparation for conception, which includes the psychological, emotional, and financial readiness of the partners. It has been found that many couples have different views on parenthood, leading to misunderstandings and conflicts. The research indicates that problems often arise due to lack of communication and consensus between spouses, psychologically unfavorable motives, stereotypical beliefs, unhealthy lifestyles, and discrepancies between partners’ behaviors and their mutual expectations. Most conflicts occur when partners have differing opinions, desires, or values and are unable to reach agreement on important issues, particularly regarding family values, shared responsibilities, and roles within the family. The influence of social stereotypes, financial difficulties, and external pressure from relatives and society on the decision to have a child is also noted. Insufficient readiness of partners for conscious pregnancy planning can lead to conflicts, as their levels of psychological preparation and motives for having children may vary significantly. Partners often face emotional alienation, inadequate communication, and lack of support for one another, complicating the planning process.In this context, it is crucial for couples to possess a solid understanding of parenthood and motherhood, to be aware of potential psychological difficulties that may arise, and to effectively apply behavioral models for successfully navigating this important period. The article also outlines prospects for further research in the area of mutual support and the development of psychological support technologies aimed at overcoming negative factors that provoke conflicts.